Study on the Occurrence of Genetic Exchange Among Parasites of the Leishmania mexicana Complex - Telittchenko, Roman; Descoteaux, Albert (Frontiers in Cellular and Infection Microbiology, 2020)
In Leishmania, genetic exchange has been experimentally demonstrated to occur in the sand fly vector and in promastigote axenic cultures through a meiotic-like process. No evidence of genetic exchange in mammalian hosts have been reported so far, possibly due to the fact that the Leishmania species used in previous studies replicate within individual parasitophorous vacuoles. In the present work, we explored the possibility that residing in communal vacuoles may provide conditions favorable for genetic exchange for L. mexicana and L. amazonensis. Using promastigotes lines of both species harboring integrated or episomal drug-resistance markers, we assessed whether genetic exchange can occur in axenic cultures, in infected macrophages as well as in infected mice. We obtained evidence of genetic exchange for L. amazonensis in both axenic promastigote cultures and infected macrophages. However, the resulting products of those putative genetic events were unstable as they did not sustain growth in subsequent sub-cultures, precluding further characterization.